Sustained mTORC1 activity during palbociclib-induced growth arrest triggers senescence in ER+ breast cancer cells. Issue 1 (2nd January 2021) - Maskey, Reeja S.; Wang, Fang; Lehman, Elyssa; Wang, Yiqun; Emmanuel, Natasha; Zhong, Wenyan; Jin, Guixian; Abraham, Robert T.; Arndt, Kim T.; Myers, Jeremy S.; Mazurek, Anthony
ABSTRACT: Palbociclib, a selective CDK4/6 kinase inhibitor, is approved in combination with endocrine therapies for the treatment of advanced estrogen receptor positive (ER+) breast cancer. In pre-clinical cancer models, CDK4/6 inhibitors act primarily as cytostatic agents. In two commonly studied ER+ breast cancer cell lines (MCF7 and T47D), CDK4/6 inhibition drives G1-phase arrest and the acquisition of a senescent-like phenotype, both of which are reversible upon palbociclib withdrawal (incomplete senescence). Here we identify an ER+ breast cancer cell line, CAMA1, in which palbociclib treatment induces irreversible cell cycle arrest and senescence (complete senescence). In stark contrast to T47D and MCF7 cells, mTORC1 activity is not stably suppressed in CAMA1 cells during palbociclib treatment. Importantly, inhibition of mTORC1 signaling either by the mTORC1 inhibitor rapamycin or by knockdown of Raptor, a unique component of mTORC1, during palbociclib treatment of CAMA1 cells blocks the induction of complete senescence. These results indicate that sustained mTORC1 activity promotes complete senescence in ER+ breast cancer cells during CDK4/6 inhibitor-induced cell cycle arrest. Consistent with this mechanism, genetic depletion of TSC2, a negative regulator of mTORC1, in MCF7 cells resulted in sustained mTORC1 activity during palbociclib treatment and evoked a complete senescence response. These findings demonstrate that persistent mTORC1 signaling during palbociclib-induced G1 arrest is a potential liability for ER+ breast cancer cells, and suggest a strategy for novel drug combinations with palbociclib.